Metabolic health is more closely associated with coronary artery calcification than obesity. - Eun-Jung Rhee (Public Library of Science (PLoS), 2013)
Background Recent studies have suggested that metabolic health may contribute more to the atherosclerosis than obesity. The aim of this study is to compare coronary artery calcium scores (CACS) among patients with different metabolic health and obesity status. Methods A health-screening program of 24,063 participants (mean age 41 years) was conducted, and CACS was assessed by multi-detector computerized tomography (MDCT). Being metabolically healthy was defined as having fewer than two of the following risk factors: high blood pressure, high fasting blood glucose, high triglyceride, low high-density lipoprotein cholesterol, highest decile of homeostasis model assessment-insulin resistance (HOMA-IR) index, and highest decile of high-sensitivity C-reactive protein (hs-CRP). Obesity status was defined as body mass index (BMI) higher than 25 kg/m(2). Analyses were performed in four groups divided according to metabolic health and obesity: metabolically healthy non-obese (MHNO), metabolically healthy obese (MHO), metabolically unhealthy non-obese (MUHNO), and metabolically unhealthy obese (MUHO). Results Mean values of CACS in the four groups were significantly different, except those between MHNO and MHO and between MUHNO and MUHO. When multinomial logistic regression analysis was performed with five CACS categories as the dependent variables and after adjusting for age, sex, and smoking status, the MHO, MUHNO, and MUHO groups showed significantly increased odds ratio for increasing CACS categories compared with no calcification status (5.221 for CACS >400 in MUHO group with 95% CI 2.856∼5.032 with MHNO group as the reference). When other variables including the metabolic parameters were included in the same model, the risks were attenuated. Conclusion Metabolic health is more closely associated with subclinical atherosclerosis than obesity as assessed by CACS.